The implication of Knowledge Transfer Project towards the understanding and skills of children’s developmental psychology among PPMS and PPMS PPKI in the district of Sabak Bernam - Janon, Nazariah Shar'ie; Abdul Khaiyom, Jamilah Hanum (UPSI Press, 2020)
PPM (Pembantu Pengurusan Murid) refers to an assistant teacher for pra-sekolah (pre-school) children while PPM PPKI (Pembantu Pengurusan Murid Program Pendidikan Khas Integrasi) is an assistant teacher for special needs children in public schools. The majority of PPMs and PPMs PPKI who have been appointed do not have the necessary qualification in child psychology or early childhood education. Despite the lack of knowledge on child psychology and special needs children, they work with these children for almost 25 hours per week. In relation to this, a project under the Knowledge Transfer Programme was conducted to provide psychological knowledge and skills to PPMs and PPMs PPKI. This study attempts to investigate whether the psychological knowledge and skills of PPMs and PPMs PPKI have increased after the project. It is hypothesized that the psychological knowledge and skills of PPMs and PPMs PPKI would have increased after the project. Fifty-four PPMs and PPMs PPKI participated in the project. Five modules of the project were delivered in five different workshops that were carried out on different dates. To know whether PPMs’ and PPMs PPKI’s knowledge and skills have increased after the project, pre- and post-assessments were conducted before and after the project. The results of paired sample t-test indicate that the overall scores of the pre-test are significantly lower than those of the post-tests: pre-programme (M=51.94, SD=2.82) and post-programme (M=58.79, SD=3.69) with t (34) =-11.11, p=0.000. The results imply that the project is effective in increasing the psychological knowledge and skills of PPMs and PPMs PPKI.